Quantification of matrix metalloproteinases MMP-8 and MMP-9 in gingival overgrowth - Jennifer Orozco-Páez; Erika Rodríguez-Cavallo; Antonio Díaz-Caballero; Darío Méndez-Cuadro (Saudi Dental Journal)
Background: Matrix metalloproteinases (MMPs) are proteolytic enzymes involved in extracellular matrix remodeling of all body tissues, including oral tissues such as gingival tissue. Expression levels of MMPs are widely studied as important biomarkers for explaining the biochemical mechanisms and evolution of many oral diseases. Objective: Demonstrate the sensitivity, reproducibility, repeatability, and robustness of the dot blot assay for the relative quantification of MMP-8 and MMP-9 expression levels in patients with GO associated with orthodontic treatment. Methods: A validated dot blot assay was used to compare the relative expression levels of MMP-8 and MMP-9 in gingival samples. Methodological variability, reproducibility, sensitivity and robustness were determined with the use of control samples from healthy donors (G1). Next, expression levels were measured in gingival tissue from patients with mild and moderate gingival overgrowth associated with orthodontic treatment (G3 and G4) and patients without gingival overgrowth but with a history of using orthodontic appliances (G2). Results: Dot blot assay demonstrated that MMP-8 and MMP-9 expression levels were higher in patients with gingival overgrowth and distinguished those with moderate clinical grade (G4) from those with mild overgrowth (G3). In addition, patients with a history of orthodontic treatment showed similar expression levels to the control group two years after removing orthodontic appliances. Conclusions: With the assay used, we were able to detect differences in MMP-8 and MMP-9 expression in patients with different levels of severity of gingival overgrowth. Dot blot could be used to measure MMPs during the onset and progression of gingival overgrowth.